Dose-response relationship of taurine on endurance cycling performance under hot and humid conditions - Li, Xinlei; Huo, Lei; Wang, Linuo; Zhang, Wenjuan (Frontiers in Nutrition, 2025)
PurposeTo investigate the effects of different doses of taurine on endurance exercise performance and physiological parameters under hot and humid conditions.MethodsThis study adopted a double-blind, randomized, placebo-controlled, cross-over design. Sixteen male university students majoring in physical education (age: 20.12 ± 1.12 years; training status: ≥3 endurance sessions/week) received 4 supplement conditions: (1) placebo (maltodextrin), (2) low-dose (1 g taurine), (3) medium-dose (4 g taurine), and (4) high-dose (6 g taurine). Participants performed a graded cycling test (initial 50 W, +50 W every 3 min at 70 rpm) until exhaustion in an environmental chamber (35 °C, 65% RH). Heart rate, core temperature, skin temperature, sweat rate, RPE, and thermal sensation were measured.ResultsCompared to placebo, time to exhaustion was significantly longer in the medium-dose group (p < 0.05), with no significant or trend-level effects in low- or high-dose groups. Blood lactate accumulation and sweating rate were higher in the medium-dose group (p < 0.05). Core temperature (9 min-End) was lower in the medium-dose group during the latter exercise phase (p < 0.05).ConclusionUnder hot and humid conditions, acute 4 g taurine supplementation enhanced time to exhaustion during graded cycling by improving thermoregulatory responses, whereas 1 g and 6 g doses showed no ergogenic effects.